Lower back pain in young climbers: a retrospective cross-sectional study - Carraro, Attilio; Gilic, Barbara; Bertolo, Riccardo; Albergoni, Andrea; Sarto, Fabio; Roklicer, Roberto; Sarto, Diego (Frontiers in Sports and Active Living, 2023)
Objective The popularity of Sport climbing has been growing since its inclusion in the Olympic Games program, which led to more people practicing it on recreational, amateur, and professional levels. Strenuous climbing training sessions and competitions might lead to frequent and serious musculoskeletal injuries and complaints among competitive climbers. This study aimed to investigate the prevalence of low back pain (LBP) and to explore the influence of various risk factors on LBP in adolescent climbers. Methods The sample included 180 competitive climbers (46.6% males) aged 13 to 19 years competing in under-U16 (…48.3%) andor U under-20 categories.Data collection was carried out using the Nordic Musculoskeletal Questionnaire (NMSQ) and the Graded Chronic Pain Scale (GCPS). Results A total of 74.4% of the entire sample of participants (male=75%; female=74%) reported lower back complaints throughout the past twelve months, and only 15.5% during the last seven days. A major part of complaints was classified as low intensity-low disability (Grade I, 62.8%; male=72.6%; female=54.2%). Under-20 competitors reported a small but significantly higher percentage of almost all NMQ measures compared to U16 under-16 athletes. Conclusions This study found a relatively high prevalence of LBP, although complaints were of limited severity and did not affect climbers' regular training practice. Moreover, climbers did not differ in LBP prevalence according to sex, while climbers from the older age group reported higher complaints and seeking medical attention than younger climbers. Future studies should prospectively monitor the influence of climbing on LBP in youth climbers.